PERGESERAN NILAI DAN FUNGSI TURUK LAGGAI PADA MASYARAKAT DESA TUAPEJAT KECAMATAN SIPORA UTARA KABUPATEN KEPULAUAN MENTAWAI SUMATERA BARAT - Yulianti, Devita; Oktavia, Dian Anggraini; Rahmad, Darmairal (Pendidikan Sosiologi, 2013)
Turuk laggai a village dance is full of symbols. First turuk laggai symbolize about  animal  life  activities,  for  the  treatment  of  ceremonies,  and  feasts  Mentawai. Now turuk laggai besides symbolize about the activities of animal life also symbolized the  social  life  of  the  community  about  the  activities  of  a  ceremonial  nature.  The problems of this research are: 1) What is the meaning turuk laggai, 2) What shape shifting value and function turuk laggai, 3) What factors are causing a shift in values and functions turuk laggai, 4) How does the existence of the villagers turuk laggai Tuapejat subdistrict North Sipora Mentawai Islands. The purpose of this study is to understand the meaning contained in turuk laggai, describe the form and function of the  value  shift  turuk  laggai,  analyzing  the  factors  that  cause  a  shift  in  values  and fngsi  turuk  laggai,  as  well  as  the  existence  turuk  laggai  currently  in  the  village  of North Sipora Sub Tuapejat Mentawai Islands. The type of data in the form of qualitative research using descriptive methods. The  technique  used  for  data  collection  are  observation,  interviews  and  document research. Informants in this study set out intentionally (purposive sampling), which consists of 22 indigenous people living in the Mentawai Tuapejat. Results of this study revealed that turuk laggai a village dance that has artistic value, sacred and mystical, which is held at each ceremony. Turuk laggai divided into two parts, namely: 1) Turuk sikerei is sacred and mystic, who works for the ceremony and punen  pulaggengan  kamateiat,  2)  turuk  simata  is  turuk  that  is  entertaining,  which serves to show punen putalimaugat. Shape shifting value and function turuk laggai is the loss of traditional ceremonies that use turuk laggai that are sacred and mystical, so turuk laggai only used for ceremonial rituals that are fun. Contributing factor is religion, government, technology, education, natural and economic conditions. While the  existence  of  the  villagers  turuk  laggai  Tuapejat  manifested  in  the  form  of management  of  Studio  Team  Ogok  Laggai  administered  by  the  Department  of Tourism Culture and Sport, held in the form of ceremonial occasions.